Fatal cardiac glycoside poisoning due to mistaking foxglove for comfrey. (9th August 2017) - Wu, I-Lin; Yu, Jiun-Hao; Lin, Chih-Chuan; Seak, Chen-June; Olson, Kent R.; Chen, Hsien-Yi
Abstract: Context: Accidental ingestion of foxglove ( Digitalis purpurea ) can cause significant cardiac toxicity. We report a patient who ingested foxglove mistaking it for comfrey and developed refractory ventricular arrhythmias. The patient died despite treatment with digoxin-specific antibody fragments (DSFab) and veno-arterial extracorporeal membrane oxygenation (VA-ECMO). Case details: A 55-year-old woman presented to the emergency department with nausea, vomiting and generalized weakness eight hours after drinking "comfrey" tea. She had bradycardia (54 beats/min) and hyperkalemia (7.6 mEq/L). Electrocardiogram revealed a first-degree atrioventricular conduction block with premature atrial contractions, followed by polymorphic ventricular tachycardia three hours after arrival. A serum digoxin level was 151.2 ng/mL. The patient developed ventricular fibrillation while waiting for Digibind infusion. Resuscitation was performed and an emergent VA-ECMO was set up. A total of eight vials of Digibind were given over the next 16 hours. She temporarily regained consciousness, but remained hemodynamically unstable and subsequently developed lower limb ischemia and multiple organ failure, and she expired on hospital day seven. A botanist confirmed that the plant was foxglove. Conclusions: The diagnosis of cardiac glycoside plant poisoning can be difficult in the absence of an accurate exposure history. In facilities where DSFab is unavailable or insufficient, early VA-ECMO might be considered in severely cardiotoxic patients unresponsive to conventional therapy.